2021
DOI: 10.31989/ffhd.v11i7.800
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of olive oil and by-products and possible innovative applications for industrial processes

Abstract: In the last few years, the production of olive oil has incredibly increased due to its beneficial properties on human health. On the other hand, the amount of waste and by-products derived from the olive oil industry has increased as well, prompting the development of new fields of research aiming to reduce disposal costs and valorize bioactive compounds from the viewpoint of the green economy. Interestingly, olive oil and by-products contain numerous molecules, including phenols, exhibiting pleiotropic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The observed growth-retardation effect of higher doses of the OLE in our study could be explained by the consortium of the different constituents as discussed above. Here, we detected that the fish group fed the 0.1% OLE and challenged with A. hydrophila exhibited the highest intestinal ALP activities either before or after the bacterial challenge in comparison to the control group, indicating improved fish disease resistance and survival rate with a lower level of igfbp mRNA expression compared to the other higher doses, which may be explained by the increased nutrient utilization at this level, thus enhancing growth and excreting antibacterial effects, in agreement with Sudjana et al [ 105 ], Gullón et al [ 106 ], and Centrone et al [ 107 ], who reported antibacterial efficacy of the OLE against Staphylococcus aureus and Escherichia coli . The increased ALP activities in the fish group treated with the 0.1% OLE in comparison to the control group strengthened the immune system’s response prior to or following the bacterial challenge and reduced the release of pro-inflammatory cytokines ( tnfα and il1β ) after the infection ( Figure 8 B,C).…”
Section: Discussionsupporting
confidence: 88%
“…The observed growth-retardation effect of higher doses of the OLE in our study could be explained by the consortium of the different constituents as discussed above. Here, we detected that the fish group fed the 0.1% OLE and challenged with A. hydrophila exhibited the highest intestinal ALP activities either before or after the bacterial challenge in comparison to the control group, indicating improved fish disease resistance and survival rate with a lower level of igfbp mRNA expression compared to the other higher doses, which may be explained by the increased nutrient utilization at this level, thus enhancing growth and excreting antibacterial effects, in agreement with Sudjana et al [ 105 ], Gullón et al [ 106 ], and Centrone et al [ 107 ], who reported antibacterial efficacy of the OLE against Staphylococcus aureus and Escherichia coli . The increased ALP activities in the fish group treated with the 0.1% OLE in comparison to the control group strengthened the immune system’s response prior to or following the bacterial challenge and reduced the release of pro-inflammatory cytokines ( tnfα and il1β ) after the infection ( Figure 8 B,C).…”
Section: Discussionsupporting
confidence: 88%
“…Olive oil has a wide range of uses in food production, especially in the Mediterranean diet. It is used as an ingredient in dressings, for cooking and frying, and even as a substitute for animal fats in meat products [ 20 , 21 , 22 ]. Due to the high content of oleic acid and significant amounts of antioxidant compounds, olive oil can be successfully used in food preparation, including thermal processes [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…substitute for animal fats in meat products [20][21][22]. Due to the high content of oleic acid and significant amounts of antioxidant compounds, olive oil can be successfully used in food preparation, including thermal processes [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Extra virgin olive oil (EVOO) is an excellent edible oil that is greatly prized for its taste and its beneficial health properties. , It consists of an Olea europaea juice obtained by mechanical procedures only, thus maintaining all of their favorable characteristics. EVOO is formed by a complex matrix of chemical compounds of two main groups.…”
Section: Introductionmentioning
confidence: 99%